EKSISTENSI NILAI SOSIAL ADA’ TUO DI DESA BATANGURU KECAMATAN SUMARORONG KABUPATEN MAMASA - Ahmad Al Yakin (Fakultas Keguruan dan Ilmu Pendidikan Univ. Al Asyariah Mandar Sulbar, 2015)
This study is based on the problem of grandeur social values There 'Tuo already eroded by globalization with the inclusion of modern culture without filtration, causing the value of Ada' Tuo will disappear so that people do not know anymore Batanguru identity. The purpose of this study was to determine the existence of social values There 'Tuo village sub-district of Batang Uru Sumarorong. Subjects In this study, the sample data sources are selected purposively and snowball sampling. The data source selected person who has authority on the social situation, including traditional leaders and religious leaders, village head, village communities Batanguru which includes natives and migrants as much as 6 residents. Methods of data collection in this study are: interview, observation and documentation. Based on the survey results revealed that social values There 'Tuo embodied in religious and social values in Batang Uru village communities to provide and regulate the relationship between the communities. Social and cultural values govern the role of each member of society and carry out any role with the people around him. The results showed that the value of social Ada'Tuo in Batang Uru village communities existence is still maintained.